Resistance to dialogic discourse in SSI teaching: The effects of an argumentation‐based workshop, teaching practicum, and induction on a preservice science teacher - Kilinc, Ahmet; Demiral, Umit; Kartal, Tezcan (Journal of research in science teaching, 2017)
Teaching socioscientific issues (SSI) necessitates dialogic discourse activities. However, a majority of science teachers prefer monologic discourse in SSI contexts. In addition, some of these teachers are resistant to change (from monologic to dialogic discourse) despite certain professional development attempts. The purpose of the present single‐case study was to investigate the nature of this resistance in a preservice science teacher (PST) (Duygu). We longitudinally followed preservice teachers through 1 year of their continuum of professional development (CPD). We administered a questionnaire including vignettes representing two types of discourse (monologic and dialogic) in SSI teaching; the participants selected one of the vignettes at four different points in their CPD: before an argumentation‐based workshop (N = 122), after the workshop (N = 6), after a SSI‐based teaching practicum (N = 5), and during the induction year (N = 1). The interviews (semi‐structured and stimulated recall) and classroom observations supported these data. We concluded that the argumentation‐based workshop decreased Duygu's resistance to dialogic discourse by producing pseudo‐changes, emergencies, and no changes in her beliefs. However, negative experiences during the teaching practicum enhanced resistance and resulted in a reversal of previous positive beliefs. Similarly, negative induction experiences contributed to her resistance by elaborating previous negative beliefs. In addition, we argue that resistance to change is a complex process exceeding the boundaries of units (e.g., discourse), subjects (e.g., SSI), and subject‐matter education (e.g., science education). The cognitive mechanisms (epistemic heuristic, evidence‐based justification, and prioritization), belief development processes (pseudo‐change, reversal, etc.), and a range of barriers (limited educational opportunities, naïve epistemologies, an argumentation‐avoider personality, etc.) produce a complex ecosystem. We believe that any effort that would be conducted to change science teachers’ teaching orientations from monologic to more dialogic versions and that does not consider this ecosystem will not thrive. © 2017 Wiley Periodicals, Inc. J Res Sci Teach 54:764–789, 2017